Analysis of Added Value and Business Feasibility in Terms of The Economic Aspect of Processing Temurui Leaf Chips (Murraya koenigii) Nusa Village, Lhoknga District - Afta Pratiwi Br Barus; Zakiah; Mustafa Usman (Nusantara Science and Technology Proceedings, 2022)
Temurui or Murraya koenigii, often also called curry leaves or koja greetings, is widely available in Aceh Province which is known in the Acehnese local language "Temurui leaves". Temurui plants are widely planted in the yards of Acehnese people's homes as ornamental plants, and the majority of Acehnese people use these plants as ornamental plants. Acehnese specialties, such as chicken catching and curry spices. So far, temurui leaves are only used for personal consumption, the rest are sold at a relatively low relevance price of IDR. 10,000 per Kg which causes this temurui leaf to be wasted so much just. Based on the analysis of the added value and business feasibility in terms of the economic aspect of processing temurui leaf chips (Murraya koenigii) in the home industry of Oen Temurui, Nusa Village, the added value of processing temurui leaves into temurui leaf chips is IDR 108,200/Kg or 54.1 percent. Economic feasibility analysis using the R/C ratio yielded 1.6 results, where the R/C value > 1 so that this business was feasible and profitable.